Field Evaluation to the attraction efficiency for the different sources of the red palm weevil aggregation pheromone - Jaddou, Marwan Ibrahim; Kaabi, Ali J.Al; Abu Agla, Abdullah M.; Al Kaabi, Ahmed S.; Al Kayoumi, Khuloud N. (Open Science Journal, 2017)
Field experiments were conducted during the periods from June, 2014 to March, 2015, in three date palm orchards located in Al Ain city, Abu Dhabi, United Arab Emirates, in order to evaluate the attraction efficacy for five different sources from the red palm weevil (RPW), Rhynchophorous ferrugineus Oliver (Coleoptera: Curculionidae), aggregation pheromone by using the standard four window black bucket trap. The three orchards are characterized by having different levels of infestation incidence by red palm weevil. The Randomize Complete Block Design (RCBD) with five treatment and three replicates was used in each of the three orchards. The aggregation pheromone sources used in this experiment were: Rhyfer 700, Pherocon RDPW Lure, Ferrugitom 700, Weevil lure, and Ferrulure +. Collectively in the three farms as well as per each farm, Weevillure aggregation pheromone trap capture significantly lower average numbers of RPW adults than Rhyfer, Pherocon, Ferrulure, and Ferrugitom pheromone sources. Rhyfer pheromone is about 1.12, 1.18, 1.56 & 1.16 % more efficient than Pherocon, Ferrugitom, Weevillure & Ferrulure, respectively.